Fish scale derived nitrogen doped hierarchical porous carbon—a high rate performing anode for lithium ion cell. (10th November 2015) - Selvamani, V.; Ravikumar, R.; Suryanarayanan, V.; Velayutham, D.; Gopukumar, S.
Abstract: Performance of nitrogen doped porous carbon, obtained from fish scale, has been investigated as an anode material for lithium ion battery in an ionic liquid (IL) electrolyte containing N-butyl, N, N, N-triethylammonium bis(trifluoromethanesulfonyl) imide (N2224 -TFSI) and in conventional medium. The N-doped fish scale hierarchical carbon (FSHC) exhibits large surface area (1980 m 2 g −1 ) with uniform pore distribution. The representative anode material shows steady state reversible capacities of ∼500 and 480 mAh g −1 at a current density of 75 mA g −1 and discharge capacities of ∼224.7 and 232.5 mAh g −1 at 2000 mA g −1 in the IL and organic electrolytes respectively for the investigated 75 cycles. Such performance indicates a coulombic efficiency of ∼90 % coupled with a superior capacity retention of about 80%. Post-mortem of the cell containing N-doped FSHC electrode cycled at high current density shows excellent stability in both electrolytes, as confirmed by Field Emission Scanning Electron Microscopy (FE-SEM) and X-ray diffraction pattern (XRD). The enhanced electrochemical performance of the N-doped FSHC as a high capacity anode for lithium-ion batteries could be mainly attributed to the high specific surface area and hierarchical porous structure.